Assisted Dying and Voluntary Euthanasia: Exploring Healthcare Professionals’ Perceptions in a Tertiary Care Setting in South India - Ashutosh Kothari; K. C. Premarajan; Adinarayanan Sethuramachandran; Sadhana Subramanian (Preventive Medicine: Research & Reviews, 2024)
Background: Globally, with the increased focus on palliative care of adding life to years, the need for the right to refuse and dignified death has also commenced. Objective: To explore the perceptions of doctors and nurses about performing assisted dying and voluntary euthanasia. Methods and Material: Participants were selected purposively to include nine health care professionals to attain information saturation. Results: The factors justifying euthanasia were the rights to choose or refuse and exclusive medical conditions. With limited medical insurance coverage, there is a thought that these factors might bring the idea of euthanasia amongst Indian people. Overall, though the healthcare professionals are not willing to perform euthanasia, they agreed to make assisted dying possible in the future but exclusively for terminally ill patients. Conclusion: It would be beneficial to standardise the terminology, have lawmakers re-examine Supreme Court of India rulings and consult medical and relevant experts on the unique situations of defining the terminally ill and what type of euthanasia may be considered.